DOI: 10.33540/292
|View full text |Cite
|
Sign up to set email alerts
|

Work-family guilt: A straightjacket keeping parents into traditional gender roles

Abstract: Work-family guilt as a straightjacket. An interview and diary on consequences of mothers' work-family guilt 3 When work-family guilt becomes a women's issue: Gender stereotypes predict high guilt among mothers but low guilt among fathers 4 How individual gender role beliefs and organizational gender cultures predict parents' work-family guilt in Europe 5 How a gendered cost-benefit analysis explains gender differences in work-family guilt 6 Appendices Nederlandse samenvatting (Summary in Dutch) References Supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
(230 reference statements)
0
3
0
Order By: Relevance
“…Consequently, mothers may be more prone than fathers to feel guilty when their work interferes with their family (i.e. work‐to‐family conflict; WFC, Aarntzen, 2020 ). Previous research indeed found that in the same WFC situation, mothers report experiencing more guilt than fathers do (Aarntzen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, mothers may be more prone than fathers to feel guilty when their work interferes with their family (i.e. work‐to‐family conflict; WFC, Aarntzen, 2020 ). Previous research indeed found that in the same WFC situation, mothers report experiencing more guilt than fathers do (Aarntzen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…work‐to‐family conflict; WFC, Aarntzen, 2020 ). Previous research indeed found that in the same WFC situation, mothers report experiencing more guilt than fathers do (Aarntzen, 2020 ). However, the question remains if these gender differences in guilt result in part from parents' internalized gender stereotypes.…”
Section: Introductionmentioning
confidence: 99%
“…When work interferes with family, it is an important source of stress for parents that can influence an individuals’ well-being ( Frone et al, 1994 ). For both male and female, high level of work-to-family conflict reduces parents’ life satisfaction, triggers more psychological stress, higher risk of burnout and higher depression ( Kossek and Ozeki, 1998 ; McNall et al, 2010 ; Aarntzen, 2020 ). Parents’ high level of pressure will be transferred to parenting behavior and emotional expression, which will virtually create a high-stress family atmosphere for young children.…”
Section: Discussionmentioning
confidence: 99%